ROLES AND EXPERIENCES OF ENGLISH EDUCATION STUDENTS IN THE SCHOOL FIELD INTRODUCTION PROGRAM (PLP) - Arbain, Muhammad; Ramadani, Fitra (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2024)
This study explores the roles and experiences of English Education students participating in the School Field Introduction Program (PLP) at Tarbiyatul Islamiyah Islamic Boarding School in Banjarmasin. The purpose of this qualitative research is to understand how student teachers adapt their teaching strategies within the unique educational and cultural environment of an Islamic boarding school. Through in-depth interviews, observations, and document analysis, the study investigates the challenges, adaptations, and teaching methods utilized by students to enhance their instructional effectiveness. Findings reveal that the students not only develop essential teaching skills but also learn to integrate Islamic values into language instruction. The PLP program provides an immersive experience, enabling student teachers to enhance their pedagogical competencies and cultural awareness. This research contributes to a better understanding of the practical training experiences in Islamic educational settings and highlights the impact of the PLP program on the professional growth of future English teachers.